The Influence of Playing Methods on Football Passing Skills at SD Negeri 2 Lokop – East Aceh - Alidin (Marga: Journal Of Innovation and Creatifity, 2023)
Learning methods are very important in supporting the success of achieving learning objectives, so this research aims to improve the soccer passing abilities of students at SDN 2 Lokop, East Aceh Regency, because there are still students who have not mastered soccer passing techniques or are not optimal. This research adopts a series of experimental methods. designed before and after testing. Data collection was carried out in this research using a football passing test. The subjects of this research were 20 students at SDN 2 Lokop, East Aceh Regency. This can be seen from the implementation of the research that the final test is better than the initial test in changing the pretest and posttest. It can be concluded that the playing method is useful for learning soccer passing skills and techniques. This level influences students' basic soccer passing abilities as a whole, including them in the good category, so that playing methods can be applied in soccer learning.